2015
DOI: 10.1158/0008-5472.can-15-0464
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Imaging of the Resection Bed Using a Handheld Probe to Reduce Incidence of Microscopic Positive Margins in Cancer Surgery

Abstract: Wide local excision (WLE) is a common surgical intervention for solid tumors such as those in melanoma, breast, pancreatic, and gastrointestinal cancer. However, adequate margin assessment during WLE remains a significant challenge, resulting in surgical re-interventions to achieve adequate local control. Currently no label-free imaging method is available for surgeons to examine the resection bed in vivo for microscopic residual cancer. Optical coherence tomography (OCT) enables real-time high-resolution imag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 22 publications
0
145
0
Order By: Relevance
“…The intraoperative HHOCT probe's size was significantly decreased by using the MEMS scanner, and the probe's functionality was tested during anastomosis performed in vivo in a mouse surgical model [91]. Moreover, a contact-based intrasurgical HHOCT probe for tumor margin analysis during human breast surgery was demonstrated in 2015 [94], and a similar probe has since been commercialized by Diagnostic Photonics, Inc [95]. The commercial probe was coupled to a 1300 nm swept-source OCT system and used a MEMS scanner to acquire images with a transverse resolution of ~15 µm over a 9 mm lateral field of view [95].…”
Section: External Intraoperative Handheld Oct Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…The intraoperative HHOCT probe's size was significantly decreased by using the MEMS scanner, and the probe's functionality was tested during anastomosis performed in vivo in a mouse surgical model [91]. Moreover, a contact-based intrasurgical HHOCT probe for tumor margin analysis during human breast surgery was demonstrated in 2015 [94], and a similar probe has since been commercialized by Diagnostic Photonics, Inc [95]. The commercial probe was coupled to a 1300 nm swept-source OCT system and used a MEMS scanner to acquire images with a transverse resolution of ~15 µm over a 9 mm lateral field of view [95].…”
Section: External Intraoperative Handheld Oct Probesmentioning
confidence: 99%
“…Large-scale clinical trials were conducted to evaluate the efficacy and safety of commercial femtosecond laser modules with OCT guidance [193], [194] and the researchers reported that OCT aided in detection of the anterior and posterior lens surfaces and iris boundaries [193], and that femtosecond laser cataract surgery with OCT guidance resulted in comparable complication rates to manual surgery [193,194]. image-based detection of cancer in in vivo resection beds and excised tissue using histopathology as a gold standard [94] (Fig. 14).…”
Section: Human Anterior Eye Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…This essentially acts like a low energy laser based "optical ultrasound" when evaluating tissue. OCT has been applied in intraoperative margin detection in cutaneous, vulvar, breast, and gastro-intestinal malignancy [47][48][49][50][51] . OCT has been examined in several diagnostic/detection applications in the head and neck such as larynx, oral, and esophageal cancer however studies examining the ability of OCT to determine the accuracy intra-operative margins are less common [20,21,49,[52][53][54][55][56][57] .…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…Since its introduction in the early 1990s, optical coherence tomography (OCT) has become an invaluable modality with widespread biomedical applications [1][2][3][4][5][6][7][8]. In particular, it is now a standard of clinical care in ophthalmology [9].…”
Section: Introductionmentioning
confidence: 99%